2017
DOI: 10.3390/molecules22010160
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Electronic Deactivation Dynamics of Xanthosine Monophosphate

Abstract: Ultrafast energy dissipation is a crucial factor for the photostability of DNA and RNA, but even some of the key electronic deactivation pathways in monomeric nucleic acid building stones are still controversial. Here, we report on the excited-state dynamics of the rare nucleotide xanthosine monophosphate as a function of deprotonation state (XMP vs. XMP−) and excitation wavelength (λpump= 278–243 nm) by femtosecond time-resolved fluorescence and absorption spectroscopy. We show that the predominating relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The relative energy levels of the ππ* state versus the nearest nπ* states affect the excited state dynamics, as shown with 2AP 18,71 . With a few exceptions (guanine, 13 isoguanine, 14 and hypoxanthine 20 ), it appears most purines (adenine, 26–31 2AP, 18 2‐oxopurine, 19 xanthine, 15,16 purine 11 ) and pyrimidines (cytosine, 74 thymine, 75,76 and uracil 77 ) relax from their initially excited ππ* to an nπ* to the ground state. Instead, 2,6‐dAP follows the 1 ππ*/S 0 CI path exclusively for 9H and both 1 ππ*/S 0 internal conversion and 1 ππ*/ 3 ππ* ISC for 7H.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The relative energy levels of the ππ* state versus the nearest nπ* states affect the excited state dynamics, as shown with 2AP 18,71 . With a few exceptions (guanine, 13 isoguanine, 14 and hypoxanthine 20 ), it appears most purines (adenine, 26–31 2AP, 18 2‐oxopurine, 19 xanthine, 15,16 purine 11 ) and pyrimidines (cytosine, 74 thymine, 75,76 and uracil 77 ) relax from their initially excited ππ* to an nπ* to the ground state. Instead, 2,6‐dAP follows the 1 ππ*/S 0 CI path exclusively for 9H and both 1 ππ*/S 0 internal conversion and 1 ππ*/ 3 ππ* ISC for 7H.…”
Section: Discussionmentioning
confidence: 94%
“…Although the picture is far from complete, there are some indications that heterosubstituted purines (e.g. guanine 13 and isoguanine 14 ) may be more photostable than the homosubstituted purines (2,6‐diaminopurine and xanthine 15,16 ), while purines with a single ligand (adenine, 17 2AP, 18 2‐oxopurine, 19 and hypoxanthine 20 ) appear to be more photostable than most purines with two ligands 13 . Martinez‐Fernandez et al 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the picture is far from complete, there are some indications that heterosubstituted purines (e.g. guanine (13) and isoguanine (14)) may be more photostable than the homosubstituted purines (2,6-diaminopurine and xanthine (15,16)), while purines with a single ligand (adenine, (17) 2AP,(18) 2-oxopurine, (19) and hypoxanthine (20)) appear to be more photostable than most purines with two ligands. (13) Martinez-Fernandez et al in a thorough computational study on the photostability effects of position and oxo/amino substitution for purines with a single ligand, (19) found that amino or oxo substitution at C 2 has little effect on the photodynamics, while C 6 functionalization leads to photostability.…”
Section: Introductionmentioning
confidence: 99%
“…Four contributions in this Special Issue investigate the electronic relaxation mechanisms in nucleic and amino acid derivatives. Röttger, Temps, and co-workers [ 24 ] examine the excited-state dynamics of the nucleotide xanthosine monophosphate in its neutral and deprotonated forms in aqueous solutions by using a combination of fluorescence up-conversion and transient absorption spectroscopy techniques with femtosecond time resolution. Gustavsson, Markovitsi, and co-workers [ 25 ] report on the time-resolved fluorescence decay and fluorescence anisotropy measurements of seven mono-, di-, and tri-methylated xanthine derivatives in water and in methanol.…”
mentioning
confidence: 99%